2012
DOI: 10.1186/1423-0127-19-79
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microRNAs in atherosclerosis and restenosis

Abstract: Atherosclerosis is commonly appreciated to represent a chronic inflammatory response of the vascular wall, and its complications cause high mortality in patients. Angioplasty with stent replacement is commonly performed in patients with atherosclerotic disease. However, the restenosis usually has a high incidence rate in angioplasty patients. Although the pathophysiological mechanisms underlying atherosclerosis and restenosis have been well established, new signaling molecules that control the progress of thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
91
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 103 publications
(117 reference statements)
2
91
0
2
Order By: Relevance
“…To examine the cell migratory capacity, 1x10 5 cells/well MCF-7 cells in each group were cultured in DMEM with 10% FBS to 100% confluence. Wounds of ~1 mm width were created with a plastic scriber and cells were washed once using PBS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine the cell migratory capacity, 1x10 5 cells/well MCF-7 cells in each group were cultured in DMEM with 10% FBS to 100% confluence. Wounds of ~1 mm width were created with a plastic scriber and cells were washed once using PBS.…”
Section: Methodsmentioning
confidence: 99%
“…By negatively mediating their target genes, miRs participate in a variety of cellular biological processes including cell growth and proliferation, survival and apoptosis, differentiation, migration and invasion (5)(6)(7)(8). Furthermore, it has been demonstrated that the deregulation of certain miRs, such as miR-375, are involved in tumorigenesis and tumor metastasis (9-11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that miRNAs are highly conserved among species and are crucial in various physiological and pathological processes, including age-associated diseases, developmental abnormalities, autoimmune diseases and various types of cancer (18)(19)(20)(21). The role of miRNAs in the cardiovascular system has been previously investigated (22,23); however, the function of miRNAs in the proliferation of VSMCs induced by TNF-α remains to be fully investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that miRNAs regulate >30% of genes, which are associated with almost all major cellular processes, including cell proliferation, differentiation, apoptosis and migration, as well as immune responses (4). Myocardial tissue injury induced by ischemia and hypoxia is a major factor underlying the development of fatal diseases.…”
Section: Introductionmentioning
confidence: 99%